Kerjasama dan konflik antara Parti Komunis Malaya dengan British Di Tanah Melayu, 1941-1948 / Ahmad Zaki Mohd Johari - Ahmad Zaki, Mohd Johari (2017)
This thesis examines the relationship between the Communist Party of Malaya (CPM) and the British Colonial Government in Malaya, from 1941 to 1948. During this period, relations between the two powers took place in two different situations. This study has proven that during the period relation between the two powers were either of conflict or political cooperation. The relationship began in the 1920s before the outbreak of the Second World War and continued when the war broke out, and the post-war era, and ended in 1948. The findings of this thesis revealing the agreement signed between the two parties and CPM participation in the Advisory Council in the Malay states during the BMA, has proved the existence of a deep connection between them. However, the relationship was not consistent and often changed and was coloured by ideological conflict influenced by a local and international politics. CPM obviously tried hard to develop the socialist-communist ideology, as well as resist British imperialism-capitalist policies. However, the early communist action was brought under control by the colonial government. In order to reinforce the findings of this thesis, various methods have been used such as library and archival research at home and abroad. Thus, various primary sources were referred to without neglecting the study of secondary sources available. Based on the primary record; some new discoveries about cooperation and conflict between the CPM and the British have been revealed through the records of colonial officials, the records of the federal government, the records of state governments, newsletters, reports, letters, private memoirs and memorandums and interviews with personalities involved directly or as an observer at the time. The results of this study could be used by all parties, both historians as well as the government in formulating policies, so that it is transparent and promotes progress and peace.